Characteristics of a national sample of victims of intimate partner violence (IPV): Associations between perpetrator substance use and physical IPV - Lund Ingunn Olea (Nordic Studies on Alcohol and Drugs, 2014)
BACKGROUND - This paper provides a characterisation of a national sample of intimate partner violence (IPV) victim shelter residents. The study also examines whether perpetrator substance use contributed to physical IPV in 2 subsamples: 1) Norwegian victims and perpetrators, and 2) immigrant victims and perpetrators. METHODS - A national sample (N=1363) of women at IPV shelters in Norway in 2011. RESULTS - The majority (62.2%) of the women had immigrant background, and social security was the most common employment/income status (42.6%). A combination of psychological and physical IPV was most frequently reported (56.1%). Perpetrator substance use was common in the Norwegian sample (57.5%). while many in the immigrant sample (47.1%) were unsure about perpetrator substance use. Perpetrator substance use was associated with physical IPV in both subsamples. CONCLUSION - Immigrant IPV victims are overrepresented in the shelter population, as are women on social security. While substance use is associated with physical IPV among Norwegians and immigrants, the association is more obvious in the Norwegian sample. The high rates of immigrant women stating they are unsure about perpetrator substance use underscore the importance that future studies address this question in a culturally sensitive matter.